Digital Transformation and Challenges in Christian Religious Education: A Critical Perspective - Hellen Lae, Yasni (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2025)
The rapid advancement of digital technology has significantly impacted educational practices, including Christian Religious Education (CRE). This article critically examines the implications of digital transformation for CRE in the current technological era. Using a qualitative descriptive approach and literature review as the primary method, the study explores strategic opportunities in integrating digital tools to enhance student engagement and comprehension. At the same time, it addresses pressing challenges such as the disruption of spiritual values, overdependence on digital media, and the erosion of interpersonal relationships in faith-based learning. The findings highlight that thoughtful and contextual use of technology is essential to ensure that digital integration aligns with the ethical and spiritual objectives of CRE. This article offers valuable insights for Christian educators in designing adaptive, reflective, and transformative pedagogical strategies.